Scaling Laws of Chain-of-Thought Reasoning in Large Language Models - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: What are the scaling laws for chain-of-thought reasoning in large language models v11. 20 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.